Occurrence of Enteropathogenic, Kanagawapositive Strains of Vibrio parahaemolyticus in Fresh Finfish and Shellfish - S., Sanjeev; Stephen, Jose (Fishery Technology, 2025)
Kanagawa phenomenon of 225 strains of Vibrio parahaemolytius isolated from fresh finfish and shellfish of marine and brackish water origin and their environments was studied. 20.56% of the isolates from different parts of finfish, 22.9% of the isolates from shellfish, 33.33% of the isolates from mud samples and 12.5% of the isolates from water samples were found Kanagawa-positive. Among isolates from different parts of finfish, 16.41% of the isolates from surface tissues, 19.05% of the isolates from gills and 36.84% of the isolates from the gut were Kanagawa-positive. All the strains of V. parahaemolyticus isolated from cooked, shucked clams were Kanagawa-negative and 50% of the isolates from mussels were Kanagawa-positive.